Boosting Lactation Naturally: The Role of Lagerstroemia Indica Leaf Infusion in Increasing Breast Milk Output - Nelly Nugrawati; Nur Ekawati; Ayu Wijaya; Andi Muhammad Adam (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
Breastfeeding offers optimal nutrition for infants, yet low milk production remains a frequent concern among postpartum mothers in Indonesia. This study examined the effect of Lagerstroemia indica leaf infusion on breast milk quantity among postpartum mothers at Puskesmas Bontomarannu. A quasi-experimental Two-Group Pretest–Posttest design involved 14 mothers assigned to intervention and control groups. The intervention group consumed the infusion twice daily for two weeks, while the control group received standard care. Breast milk volume was measured using standardized pumping techniques. Paired t-tests showed a significant increase in milk volume in the intervention group (66.25 ml to 90.00 ml; p = 0.010) compared with the control group (64.38 ml to 74.38 ml; p = 0.027). Independent t-test results confirmed a significant posttest difference between groups, indicating the effectiveness of the infusion in enhancing milk production. These findings suggest that Lagerstroemia indica infusion may serve as a practical and affordable galactagogue for postpartum mothers. However, the small sample size limits generalizability and necessitates further research with larger populations.